Answer:
(x + 1)² + (y - 3)² = 8
Step-by-step explanation:
radius (r): √(1 - (-1))² + (1 - 3)² = √8 = 2√2
Formula for circle with center (h,k): (x – h)² + (y – k)² = r²
(x + 1)² + (y - 3)² = 8
Answer:
PA) 8
PB) 45
Step-by-step explanation:
PA) Find the prime factors of each term in order to find the greatest common factor (GCF).
8
PB)
Step 1:
(8 x 5) + (16 x -1)
Step 2: Multiply
40 + 15
Step 3: Add
45
Answer:
Option D is right,.
Step-by-step explanation:
-a+4b+2c=-8 ... i
3a+b-4c=9 ... ii
b=-1 ... iii
Substitute the value of b, in i and ii
-a-4+2c =-8 or -a+2c = -4
and 3a-1-4c = 9 or 3a -4c =8
Now we have two equations in two variables
-a+2c =-4 and 3a-4c =8
a = 2c+4: substitute this in the other equatin.
3(2c+4)-4c =8 Or 2c +12 =8
2c =-4 or c = -2
Substitute in -a+2c =12
-a-2 = -4
a = -2+4 =2
a=2, b=-1 and c =-1 is the solution.